AUTOMATION APPLIED TO INDUSTRIAL MAINTENANCE - Brandini, Ademilson Donizete; da Silva, Gilson José (Revista Interface Tecnológica, 2022)
The new technologies of the fourth industrial revolution have enormous benefits. By analyzing the data stored in your systems, processes can continually improve. This also allows for better maintenance schedules and lower risk of unplanned system failures. Consequently, increases in productivity allow production chains to have immense dynamism. Within this context, the objective of this work is to evaluate the impact of automation and its technologies on industrial maintenance. For this, a bibliographic research was carried out through the analysis of books and articles on the subject. It is possible to conclude that maintenance workers are included in the growing effects of industrial automation. The low costs of building automated systems make it possible for more processes to be automated. Due to resistance to new methods, many activities within maintenance generally do not adopt changes. However, the implementation of computerized systems has managed the tasks through automation in the maintenance process. This includes data collection, management, analysis, inventory scheduling, resource allocation and work orders. Automation has impacted maintenance, improving productivity, security and overall data management.